Edukasi Hidup Sehat bagi Siswa SDN 93 Kendari bersama Puskesmas Mokoau - Wahyuni, Wahyuni; Fitrawan, La Ode Muhammad; Pascayantri, Asniar; Mutmainah A., Nur; Wijaya, Rawiyatin; Hartinah, Sitti; Aprilia, Yuyun; Veragita, Elsa; Fathonah, Annisya Syamsah Hizyar; MR, Muhammad Fauzan.; Jalil, Intan Permatasari (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Young children are highly sensitive to their surroundings and tend to imitate the behavior of the adults around them. Therefore, education and the habit of clean and healthy living from an early age are very important in forming positive habits and preventing disease in the future. This activity was carried out in collaboration with the Mokoau Community Health Center through counseling students on how to live healthily to prevent intestinal worms, diarrhea, and infectious diseases at school and at home, with the help of leaflets. The results of this activity showed an increase in students' knowledge about the prevention of intestinal worms, diarrhea, respiratory infections, and measles. They understood that intestinal worms can be transmitted through dirty soil or food and the importance of maintaining personal hygiene, such as washing hands and wearing footwear. This improvement was evident during the discussion session, when students were able to answer questions correctly and explain how to prevent these diseases. In addition, students were also able to practice proper hand washing and apply coughing and sneezing etiquette.